Calidad del servicio turístico en el área de conservación privada “Bosque Natural El Cañoncillo” - Delgado Abanto, Jasmin Anais (2019)
This thesis aims to determine the quality of the tourist service with the satisfaction of _x000D_ the visitors in the Private Conservation Area “Natural forest El Cañoncillo”, through the fulfillment of the dimensions tangible elements, reliability, responsiveness, security and empathy. Visitor satisfaction was found to be high with 70% of all five dimensions: tangible elements, reliability, responsiveness, security and empathy. Highlighting the dimensions that stand out with the security and empathy both with 75% of high valuation, highlighting each of them an element that is sufficient knowledge to answer questions with 77% and empathy the friendliness of the staff with 83%, followed by the tangible elements with 73% highlighting in this dimension the physical appearance of the staff with 77%, response capacity with 67% excelling the fast service with 72% and reliability with 62% prevailing the service component at the first time with 69%. _x000D_ Methods such as the analytical-synthetic method and ethnographic method were used; as for the techniques were used: The interview, the survey, signing and direct observation; The instruments were interview questionnaire, survey questionnaire, camera, recorder and field notebook. We applied the questionnaire of 22 questions of the model SERVPERF to measure the satisfaction to 245 visitors after receiving the service.